2012
DOI: 10.1016/j.ecoenv.2011.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers in Senegal sole, Solea senegalensis, to assess the impact of heavy metal pollution in a Huelva estuary (SW Spain): Seasonal and spatial variation

Abstract: The response of wild fish to heavy metals was studied in sole (Solea senegalensis) collected in 2004, 2005 and 2006 at three sampling sites from Huelva estuary (SW Spain), in the vicinity of a petrochemical and mining industry. Heavy metals As, Cd, Cu, Fe, Pb and Zn were analyzed in samples collected from sediment, water and tissue (liver) to examine their bioconcentration and effects in fish such as lipid peroxidation (LPO), catalase (CAT; EC 1.11.1.6), glutathione peroxidase (GPx; EC 1.8.1.7), glutathione S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 62 publications
(56 reference statements)
1
37
0
Order By: Relevance
“…Considering that both enzymes had their activities significantly induced during warmer periods, which coincided with anabolism/biosynthesis of reserves, it is possible to sustain the occurrence of conditions more favorable to oxidative stress. This is a pattern already demonstrated for other marine fish species, including Zoarces viviparous (Heise et al, 2007), Solea senegalensis (Oliva et al, 2012), and Mugil cephalus (Padmini and Vijaya Geetha, 2009). The discussion of both biomarkers is intrinsically connected, since CAT and GSTs may give further insights into physiological oxidative processes.…”
Section: Wwwfrontiersinorgmentioning
confidence: 80%
“…Considering that both enzymes had their activities significantly induced during warmer periods, which coincided with anabolism/biosynthesis of reserves, it is possible to sustain the occurrence of conditions more favorable to oxidative stress. This is a pattern already demonstrated for other marine fish species, including Zoarces viviparous (Heise et al, 2007), Solea senegalensis (Oliva et al, 2012), and Mugil cephalus (Padmini and Vijaya Geetha, 2009). The discussion of both biomarkers is intrinsically connected, since CAT and GSTs may give further insights into physiological oxidative processes.…”
Section: Wwwfrontiersinorgmentioning
confidence: 80%
“…Several other studies reported no induction by trace metals of the antioxidant system (Eyckmans et al 2011;Heier et al 2013;Kelly and Janz 2009;Marques et al 2013). However, many other reports mentioned antioxidant system alterations caused by exposure to trace metals (Barillet et al 2011;Fernandez-Davila et al 2012;Heier et al 2013;Maria et al 2009;Oliva et al 2012a;Qu et al 2014;Sanchez et al 2007) or stimulations of some of these proteins and enzymes (Andersen et al 1998;Eyckmans et al 2011;Fernandez-Davila et al 2012;Kelly and Janz 2009;Vieira et al 2012). Effects of metals on fish antioxidant responses depended on the dose, the route of exposure and the lag time between the start of exposure and antioxidant system analyses.…”
Section: Effects On Biologic Parametersmentioning
confidence: 96%
“…The enzyme response to pollutants shows a bell-shaped trend, with an initial increase in activity due to the activation of enzyme synthesis followed by a decrease in enzymatic activity, due to the enhanced catabolic rate and/or a direct inhibitory action of toxic chemicals on the enzyme molecules (Viarengo et al 2007). Thus, high CAT activities found in mussels and fish at polluted sites are considered an adaptive response to ROS-inducing contaminants (Roméo et al 2003;Cappello et al 2013;Jebali et al 2013) whereas low CAT activities at polluted sites are linked with increased susceptibility to oxidative stress (Regoli et al 2004;Pampanin et al 2005a;Oliva et al 2012). Accordingly, the low CAT activities observed in this 16 study in mussels collected from the impacted sites suggest oxidative stress experienced by these animals.…”
Section: Discussionmentioning
confidence: 63%